Odpowiedzi

  • Użytkownik Zadane
2009-11-26T15:33:58+01:00
A) a-[a-(1-a) = a-[a-1+a]=a-a+1-a=-3a+1
b) -x-[-(1-x)-(x-1)]=-x-[-1+x-x+1]=-x+1+x-x+1=-x+2
c) x-[y-(x-y)-x-(y-x)]= x-[y-x+y-x-y+x]= x-y+x-y+x+y-x=2x-y
d) 1-a-[1-(a-1)-2a-(1-3a)-a-1=1-a-[1-a+1-2a-1+3a-a-1]=1-a-1-a-1+2a+1-3a+a+1=-2a-1
2009-11-26T15:39:27+01:00
A) a-[a-(1-a)= a-[a-1+a]=a-a+1-a=1-a
b) -x-[-(1-x)-(x-1)]=-x-[-1+x-x+1]=-x+1-x+x-1=x
c) x-[y-(x-y)-x-(y-x)]=x-[y-x+y-x-y+x]=x-y+x-y+x+y-x=2x-y
d) 1-a-[1-(a-1)-2a-(1-3a)-a-1=1-a-[1-a+1-2a-1+3a-a-1]= =1-a-1+a-1+2a+1-3a+a+1=1